Bacterial lysate therapy for the prevention of wheezing episodes and asthma exacerbations: a systematic review and meta-analysis. (27th November 2020) - de Boer, Geertje Maria; Żółkiewicz, Jakub; Strzelec, Konrad Piotr; Ruszczyński, Marek; Hendriks, Rudi W.; Braunstahl, Gert-Jan; Feleszko, Wojciech; Tramper-Stranders, Gerdien. A.
Wheezing and asthma are a growing cause of morbidity in children and adults. Treatment is aimed at prevention of disease exacerbations and preservation of lung function. Respiratory viruses are involved in ∼40–60% of exacerbations. Bacterial lysates prevent recurrent respiratory tract infections and might reduce exacerbations. Moreover, immunomodulatory effects have been observed in human and animal studies. Here we aimed to assess the effects of bacterial lysate therapy on preschool wheezing episodes and asthma exacerbation frequency. We performed a systematic literature review based on the Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) statement and a meta-analysis using Cochrane Review Manager. Out of 2016 retrieved articles, 22 studies were included, of which five provided sufficient data for a meta-analysis. The use of bacterial lysates showed a decrease of both wheezing episodes (mean difference −2.35 (−3.03– −1.67), p<0.001) and asthma exacerbations in children (mean difference −0.90 (−1.23– −0.57), p<0.001). Additionally, antibiotic use was reduced, and the duration of wheezing episodes was also decreased. No data for adults with asthma are currently available. The immunomodulatory effect seems to be dependent on increased T-helper (Th)1-cell activation and Th2-cell suppression. These favourable effects of bacterial lysates indicate that they show promise as add-on therapy in preschool wheezing and childhood asthma. Bacterial lysates reduce the number of respiratory tract infections by immune modulation; we show evidence for prevention of wheezing episodes and asthma exacerbations by bacterial lysates. Thus, they might be a promising add-on therapy in asthma. https://bit.ly/3dunDLG